2013
DOI: 10.1159/000350934
|View full text |Cite
|
Sign up to set email alerts
|

Atypical Microorganisms in Expressed Prostatic Secretion from Patients with Chronic Prostatitis/Chronic Pelvic Pain Syndrome: Microbiological Results from a Case-Control Study

Abstract: Objectives: To investigate the microorganisms in expressed prostatic secretions (EPS) of both chronic prostatitis patients and normal young male adults and to determine which microorganisms are associated with the degree of intraprostatic inflammation. Methods: Specific polymerase chain reaction (PCR) technology was performed to confirm Neisseria gonorrhoeae, Mycobacterium tuberculosis, Mycoplasma and Chlamydia trachomatis as well as human papilloma virus (HPV), herpes simplex virus type 2 (HSV-2) and cytomega… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
20
0
7

Year Published

2014
2014
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 16 publications
1
20
0
7
Order By: Relevance
“…A recent study has identified CMV, among other microorganisms, in the expressed prostatic secretion from men with CPPS III. The total number of bacteria and/or viruses detected by a PCR assay was significantly associated with both disease severity and leukocyte count in expressed prostatic secretion (Xiao et al ., ). The high prevalence of CMV in men with infertility associated with chronic IUTD can be explained by viral effects on prostate and epididymal function.…”
Section: Discussionmentioning
confidence: 97%
“…A recent study has identified CMV, among other microorganisms, in the expressed prostatic secretion from men with CPPS III. The total number of bacteria and/or viruses detected by a PCR assay was significantly associated with both disease severity and leukocyte count in expressed prostatic secretion (Xiao et al ., ). The high prevalence of CMV in men with infertility associated with chronic IUTD can be explained by viral effects on prostate and epididymal function.…”
Section: Discussionmentioning
confidence: 97%
“…diagnostics of atypical microorganisms in patients with chronic prostatitis/chronic pelvic pain syndrome [32]. Sequencing methods do not allow (1) to differentiate between alive and dead bacteria, (2) to detect the level of bacteriuria, or (3) to determine the bacterial antibiotic susceptibility.…”
Section: Discussionmentioning
confidence: 99%
“…All patients and healthy controls underwent a comprehensive andrological work-up including blood withdrawal, a standardized 2-glass test providing first-void urine and a postprostatic massage urine, a semen analysis and assessment of symptoms using the chronic prostatitis symptom index (NIH-CPSI) [21] . Exclusion of bacterial infection was performed by culture and molecular diagnostics, using gene amplification analysis [22,23] . Finally, 105 patients diagnosed with CP/CPPS type IIIb (mean age 42 ± 13, <10 leukocytes in expressed prostatic secretion or post prostate massage urine) and 41 healthy volunteers without any preexisting urological conditions (mean age 25 ± 3.4) were recruited in the Clinic of Urology, Pediatric Urology and Andrology, Giessen, Germany.…”
Section: Collection Of Blood and Semen Samplesmentioning
confidence: 99%